COVID-19 infection during the Olympic and Paralympic Games Tokyo 2020 - Yashio, T.; Murayama, A.; Kami, M.; Ozaki, A.; Tanimoto, T.; Rodriguez-Morales, A. J. (Travel Medicine and Infectious Disease, 2021)
From July to September 2021, the Olympic Games Tokyo 2020 (OGT) and Paralympic Games Tokyo 2020 (PGT) were held after a one-year postponement. The number of participants from outside Japan was estimated as 71,000, including 11,656 OGT and 4403 PGT athletes [1].